Improved Package of Practices for Poplars under Agroforestry - Lal, Piare (Indian Forester, 1991)
Certain clones of exotiC poplar P. deltoldes have been found to be extremely fat growing and well adapted for farm forestry plantations under irrigated conditions In northwestern plains of Uttar Pradesh, parts of Haryana and Punjab. Avaliability of long term bank loans and possibility of good economiC returns at short rotations of 8 years and multiple industrial Uses of poplars have made them extremely popular with farmers. More than 10,000 farmers have already planted 18,320 has with poplars under agroforestry in Uttar Pradesh, Haryan and Punjab states. Improved package of practices for nursery raising, selection of suitable sites, transplanting operstions and maintensnce of poplar plantations have been described for improving yields, quality of timber and economic returns.